.IMPLEMENTASI FUZZY ANP PADA PEMILIHAN JASA EKSPEDISI - Malfin Okta sayoga Hadinata; rini oktavera (Institut Teknologi Adhi Tama Surabaya, 2022)
Today, the dynamic development of the business world and the rapidly increasing population growth rate encourage the increasing flow of goods and the movement of people. Besides, the rapid development of information technology adds to the diversity of people's choices for online-based delivery of goods. Every online transaction of goods requires the support of a logistics courier service to deliver. Large logistics courier service companies that can handle inter-city and inter-provincial deliveries include Tiki, JNE and JT. To handle expensive and quite vulnerable goods, they need a lot of criteria and accuracy in choosing logistics services. This study aims to determine the expedition service desired by the community using the Fuzzy ANP method. It begins with determining the criteria and factors influencing the decision to choose a freight forwarder or community expedition service from the criteria of quality, price, trust and service. Furthermore, of the three choices of expedition services based on FANP, the most popular among the public are JNE, JT and TIKI.